THE ROLE OF SOFT MOBILITY TOWARDS STRENGTHENING URBAN TRANSFORMATION AND SUSTAINABLE WELL-BEING: CASE STUDY: MANSOURA CITY, EGYPT - Mai Madkour; Alaa ELMANZLAWI (Journal of Engineering Research - Egypt)
This research investigates the method of soft mobility role on Egyptian neighborhood unit. It discusses itsrelationship with the main principles of New Urbanism. And proposes some objectives: Interpret Mobilitynew concepts in New Urbanism, cite urbanism principles and its trends to conclude soft mobility indicators,design a matrix inventories the compatibility of soft mobility indicators and behavioral dimension. And atlast, the matrix tests the combination of indicators and dimensions in an Egyptian traditional urban fabric,at Mansoura City.